PERLINDUNGAN HUKUM BAGI PEMBELI PADA PT. NEW VILLA GREEN PADAT KARYA INDAH JALAN PADAT KARYA LOA BAKUNG KOTA SAMARINDA (PERUMAHAN UNIT TERBATAS) - Aldila Wijayanti Putri (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTHousing as one of the basic needs in humans, both as a unit with fellow natural environment. This natural relationship is the place to be and at the same time the means that support and provide the materials needed for property ownership as regulated in the 1945 Constitution in chapter X, which is included in Human Rights which has regulated those relating to property ownership as contained in Article 27 Paragraph 1 which reads: